2007
DOI: 10.2174/156802607779318343
|View full text |Cite
|
Sign up to set email alerts
|

PDZ Domain Protein-Protein Interactions: A Case Study with PICK1

Abstract: Using PICK1 as an example this review highlights PDZ domains support a repertoire of protein-protein interactions that regulate the subcellular localisation and function of receptors, ion channels and enzymes. PICK1 is a 416 amino acid protein that contains a PDZ domain, a coiled-coil motif/arfaptin homology domain and an acidic c-terminal. Nearly all proteins thus far reported to interact with PICK1 do so via its single PDZ domain. PICK1 self-associates via its coiled-coil motif and together with its PDZ doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 231 publications
(400 reference statements)
0
30
0
1
Order By: Relevance
“…We focused on PICK1 because it is an important dimeric scaffolding protein widely expressed in the CNS (33) and because recent studies have suggested that the PICK1 PDZ domain might be an appealing drug target in relation to at least three cases involving dysfunction of AMPA receptor regulation and representing three unmet medical needs. In relation to neuropathic pain, it was observed that disruption of the interaction with the AMPA receptor by intrathecal injection of membrane-permeable PICK1-specific peptides alleviated neuropathic reflex sensitization induced by chronic constriction injury (13).…”
Section: Discussionmentioning
confidence: 99%
“…We focused on PICK1 because it is an important dimeric scaffolding protein widely expressed in the CNS (33) and because recent studies have suggested that the PICK1 PDZ domain might be an appealing drug target in relation to at least three cases involving dysfunction of AMPA receptor regulation and representing three unmet medical needs. In relation to neuropathic pain, it was observed that disruption of the interaction with the AMPA receptor by intrathecal injection of membrane-permeable PICK1-specific peptides alleviated neuropathic reflex sensitization induced by chronic constriction injury (13).…”
Section: Discussionmentioning
confidence: 99%
“…Protein interacting with C kinase 1 (PICK1) 2 is a widely distributed dimeric scaffolding protein characterized by the presence of a single N-terminal PSD-95/Discs large/ZO-1 (PDZ) homology domain in each protomer (1,2). The PDZ domain was originally found to bind the extreme C terminus of protein kinase C␣ (PKC␣) (3,4); however, later, the PDZ domain was shown to also bind the C termini of several other proteins (2,5).…”
mentioning
confidence: 99%
“…This is distinct from scFv-based proteins that reduce Gephyrin expression through an unknown mechanism, with unknown off-target effects 30 . In addition, because the Gephyrin FingR was specifically engineered to bind Gephyrin with very high affinity and specificity, the fidelity with which it degrades its target is likely to be much higher than that of a system that depends on naturally occurring protein-protein interactions, such as those involving PDZ domains, which have relatively low affinity and specificity 31,32 . Furthermore, positively charged cell-permeant peptides such as Tat, upon which systems mediating degradation with peptides rely, are inefficient, unstable, and induce cytotoxicity 33 .…”
Section: Discussionmentioning
confidence: 99%